Single-Molecule Detection of Optical Signals Using DNA-Based Plasmonic Nanostructures - Renjie Niu; Jintian Shao; Mingnan Wu; Chang Liu; Jie Chao (Biosensors, 2025)
Single-molecule optical signal detection provides high sensitivity and specificity for the detection of biomolecules and chemical substances, which is of significant importance in fields such as biomedicine, environmental monitoring, and materials science. In recent years, DNA-based plasmonic nanostructures have emerged as powerful tools for achieving single-molecule optical signal detection due to their unique self-assembly properties and excellent optical performance. In particular, DNA origami technology enables the precise construction of metallic nanostructures with specific shapes and functions, which can effectively enhance the interaction between light and matter, thereby significantly increasing signal intensity and detection sensitivity. Furthermore, the programmability of DNA not only simplifies the implementation of single-molecule operations but also allows researchers to design and optimize nanostructures according to specific detection requirements. This review will explore the applications of DNA-based plasmonic nanostructures in single-molecule optical signal detection, including surface-enhanced Raman spectroscopy and enhanced fluorescence for single-molecule signal detection. We will analyze their working principles, advantages, current research progress, and future research directions. By summarizing the work in this field, we hope to provide references and insights for researchers, contributing to the advancement of biomedicine and environmental monitoring.